Two homes - Masurel, Claire; Denton, Kady MacDonald (Cambridge, MA : Candlewick Press, 2001)
A young boy named Alex enjoys the homes of both of his parents who live apart but love Alex very much.
Keywords: Children of divorced parents -- Fiction; Divorce -- Fiction; Parent and child -- Fiction; Dwellings -- Fiction